Assessment of Anatomical Variations and Surgical Techniques in Ethnic Blepharoplasty in the Hazara Community: A Cross-Sectional Study - Kamal Uddin Khan, Farzana Abdullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Blepharoplasty aims to enhance the appearance and function around your eyes. Many people choose blepharoplasty worldwide since it helps improve droopy eyelids caused by dermatochalasis, fat protruding through the lid margin and ptosis. Ethnic blepharoplasty aims to address extra skin and fat, while also helping to keep or even enhance common Asian traits like the fold above the eyelid and the fullness beneath it. Materials & Methods: A cross-sectional study was conducted from January 2023 to June 2023 under the guidelines of Hilinski declaration, after getting ethical approval from institutional review board of the Hospital. In this study, a total of 50 patients of Hazara ethnic group with the age range of 18 to 50 years of age undergoing for blepharoplasty were recruited after getting prior written informed consent. Results: A total of 50 patients (35 females and 15 males) of Hazara ethnicity underwent blepharoplasty with the mean age of 34.7 ± 8.5 years. Study participants were assessed for anatomical variations, which included thick upper eyelid skin (76%, n=38), low supratarsal crease (62%, n=31), prominent medial epicanthal folds (54%, n=27), and lower eyelid fat herniation (48%, n=24). The mean GAIS score was 4.3 ± 0.5, indicating significant aesthetic improvement. Conclusion: This study proves that using ethnic-specific knowledge and different surgical methods for Hazara patients in blepharoplasty achieves the best results. Mixing conservative fat removal with proper incisions and the support of extra techniques allows surgeons to make patients happy and avoid many complications. Keywords: ethnic blepharoplasty, Hazara community, eyelid, suprasternal crease, epicanthal folds.